Managing Digital Platforms in User Organizations: The Interactions Between Digital Options and Digital Debt - Rolland, Knut H.; Mathiassen, Lars; Rai, Arun (Information Systems Research, 2018)
As organizations increasingly use digital platforms to facilitate innovation, researchers are seeking to understand how platforms shape business practices. Although extant literature offers important insights into platform management from a platform-owner perspective, we know little about how organizations manage industry platforms provided by external parties to generate opportunities and overcome challenges in relation to their infrastructure and work processes. As part of larger ecosystems, these digital platforms offer organizations bundles of digital options that they can selectively invest in over time. At the same time, organizations’ previous investments in digital infrastructure and work processes produce a legacy of digital debt that conditions how they manage their digital platforms over time. Against this backdrop, we investigate how digital options and digital debt were implicated in a large Scandinavian media organization’s management of a news production platform over nearly 17 years. Drawing on extant literature and the findings from this case, we theorize the progression of and interactions between digital options and digital debt during an organization’s digital platform management in relation to its infrastructure and work processes. The theory reveals the complex choices that organizations face in such efforts: While they may have to resolve digital debt to make a platform’s digital options actionable, hesitancy to plant digital debt may equally well prevent them from realizing otherwise attractive digital options. Similarly, while identified digital options may offer organizations new opportunities to resolve digital debt, eagerness to realize digital options may just as easily lead to unwise planting of digital debt.